Transportable system for on‐site calibration of permafrost temperature sensors. (18th May 2020) - Merlone, Andrea; Sanna, Francesca; Coppa, Graziano; Massano, Laura; Musacchio, Chiara
Abstract: Evaluating the degradation of permafrost is a major challenge in understanding global warming and its impact on the cryosphere. The Global Cryosphere Watch is promoting actions towards data quality and traceability, to achieve comparability of observations from different permafrost stations. In response to this, a transportable system for on‐site calibrations of permafrost temperature sensors was studied, developed and tested in the field, within the project MeteoMet. The system, here described, allows users to establish metrological traceability to permafrost temperature profiles, by performing the calibration on‐site, even in remote or high‐elevation areas, in realistic conditions. A field campaign at 3, 000 m elevation to test the system's performance and practical use is also reported. Overall calibration uncertainty in the field accounted for <0.05 °C, with contribution from reference sensors within 2 mK over the whole range; besides reducing uncertainties in each measuring point of a chain, the procedure also allows users to establish comparability among all the sensors within 0.03 °C. The self‐heating effect of each sensor was also evaluated as 0.007 °C, and was thus considered a negligible component. The evolution of permafrost thawing can be more robustly evaluated, through documented data traceability together with improved comparability in space and time.